The distal radial decompression osteotomy for ulnar impingement syndrome - Krimmer, Hermann; Unglaub, Frank (Archives of orthopaedic and trauma surgery, 2016)
Introduction: The decompression of the distal radioulnar joint (DRUJ) is performed by ulnar translation of the radial shaft proximal to the sigmoid notch, i.e. detensioning of the distal part of the interosseous membrane (DIOM) while containment of the DRUJ is achieved by closed wedge osteotomy of the radius. The osteotomy shortens the radius which entails detensioning of the triangular fibrocartilage complex (TFCC). Surgical technique: Facilitating the modified Henry approach to the distal palmar radius a radial based wedge osteotomy is applied. The proximal osteotomy is proximal to the ulnar head and distal osteotomy is proximal to the sigmoid notch to prevent iatrogenic impingement. Ulnar translation of the radial shaft is performed to loosen the DIOM. The closed wedge osteotomy reduces radial inclination which will foster containment of the DRUJ. Conclusion: Distal radial decompression osteotomy of the DRUJ preserves DRUJ function while relieving painful impingement. Further surgical interventions are not compromised in case of failure.
Gesehen am 14.01.2019
Published online: 23 November 2015